Endobronchial metastasis as first manifestation of renal cell carcinoma - Kaneko, Yoshiko (Radiology and oncology (Ljubljana), 2003)
Background. In the majority of cases of endobrunchial metastasis, presence of a primary tumour antedated the diagnosis of the metastasis. We showed a case of endobronchial metastasis as first manifestation of renal cell carcinoma. Case report. A 61-year old man was admitted to our hospital complaining of cough of 3 months duration. Chest CT scan showed a polypoid mass in the right upper lobe bronchus. Biopsy of the lesion was obtained, and microscopic examination showed metastatic renal cell carcinoma of the bronchial wall. Conclusions. When endobronchial lesion occurs in the absence of clinical evidence of a primary tumour, appropriate diagnostic studies should be undertaken to exclude the possibility of an asymptomatic extrathoracic tumour.
Keywords: Bronchial Neoplasms; Bronhialne novotvorbe; Carcinoma, Renal Cell; karcinom; Karcinom ledvičnih celic; Kidney Neoplasms; Ledvica, novotvorbe; ledvice; metastaze; Middle Age; Neoplasm Metastasis; Novotvorba, metastaza; pljuča; rak (medicina); Secondary; Srednja leta